1977
DOI: 10.1037/0096-1523.3.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Reaction times in a bisensory task: Implications for attention and speech perception.

Abstract: Reading reaction time (RT) to visual stimuli was shown to vary according to the nature of simultaneous auditory stimuli. In Experiment 1, simultaneous different digits produced slower RTs than a burst of speech noise, while identicaly digits produced faster RTs. In Experiments 2 and 3 the stimuli were phoneme pairs which differed on either zero, one, or two articulatory features. Identical phonemes resulted in the fastest RTs. The RTs to non-identical phoneme pairs were not directly related to the number of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Conversely, inconsistent secondary stimulation may interfere with primary processing. Thus in a study in which the primary task was to respond to a visual digit, Mynatt (1977) found that reaction time was facilitated when the auditory secondary stimulus was the same digit and was impaired when it was a different digit (both relative to the level for a random noise stimulus). In addition, similar results are obtained when the latency of the P300 event-related brain potential (see Price & Smith, 1974) is measured (Squires, Donchin, Squires, & Grossberg, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inconsistent secondary stimulation may interfere with primary processing. Thus in a study in which the primary task was to respond to a visual digit, Mynatt (1977) found that reaction time was facilitated when the auditory secondary stimulus was the same digit and was impaired when it was a different digit (both relative to the level for a random noise stimulus). In addition, similar results are obtained when the latency of the P300 event-related brain potential (see Price & Smith, 1974) is measured (Squires, Donchin, Squires, & Grossberg, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when an unattended auditory digit is the same as an attended visual digit, naming performance is facilitated relative to a silent or noise-burst control (Greenwald, 1970;Mynatt, 1977). It has also been found in tasks involving words that naming latency is facilitated when an identical cross-modal word is presented simultaneously with the word to be named (Posner, Lewis, & Conrad, 1972).…”
mentioning
confidence: 92%
“…In the phonological task, subjects were instructed to decide whether or not the attended word contained Prior research (Greenwald, 1970;Lewis, 1972;Mynatt, 1977) has shown that semantically related material in an unattended modality, such as the situation here for BOTH trial types, produced interference in task performance. But it must be remembered that in the previous studies the response was to pronounce the attended stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, when an unattended auditory digit is the same as the attended visual digit, pronunciation latency for the digit is facilitated (Greenwald, 1970;Mynatt, 1977). It has also been shown that unattended visual (Lewis, 1972) and auditory (Greenwald, 1970;Mynatt, 1977) words and digits interfere with pronunciation of items presented to the attended modality when the attended and unattended items are semantically related. This influence of semantically related unattended words indicates automatic activation of a semantic code that is shared by the two modalities.…”
mentioning
confidence: 95%
See 1 more Smart Citation